(untitled) - Molloy, Derek (Indianapolis, IN, 2016)
This book favors engineering principles over a 'recipe' approach to give you the skills you need to design and build your own projects. You'll understand the fundamental principles in a way that transfers to any type of electronics, electronic modules, or external peripherals, using a "learning by doing" approach that caters to both beginners and experts.
Keywords: Raspberry Pi (Máy tính),Raspberry Pi (Computer); Lập trình,Programming